Writing the Native American: An Overview of the Works of Alexie, King and Vizenor - Asma Mansoor (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This survey paper offers an overview of the primary concerns of contemporary Native American writers as they unravel what it means to be Native American in the contemporary world. It unpicks the complexities of Native American identity and its entanglements with a multi-layered past, its sense of deracination as well linguistic and cultural erasure. In so doing, it uses stories to highlight the Native American identity as a fluid construct that goes beyond its confinement within a stereotypical victimology. However, even as they negotiate with the Us/Other binary, Native American writers do not forfeit their awareness and demand for self-respect in their socio-political circumference. Story-writing is, in effect, a means for them to articulate this awareness and also to transmute it into a collective human experience.